PERBANDINGAN KEBERHASILAN PERSALINAN ANTARA MISOPROSTOL DAN FOLEY KATETER PADA POSTTERM - Wulandari, Isnamaya Kartika; Sumarah, Sumarah; Margono, Margono (Poltekkes Kemenkes Yogyakarta, 2012)
Based on former study in Wates General Hospital 2011 there are data of total induction labor 367 (29,24%) of 1255 vaginal delivery, where is 3 induction methods used such as misoprostol are 139 patient (37,87%), foley catheter are 125 patient (34,06%) and oxytocin are 103 patient (28,07%) with different success level in vaginal delivery. induction labor is one of active intervention which have potential for the fetus and mother, but it can increase the risk like section-cesarean delivery, abnormal fetus heartbeat, multiple study of misoprostol induction by oral and foley catheter have different result. To identify success comparison of vaginal delivery used misoprostol by oral for induction and foley catheter for women with post term in Wates General Hospital 2012. This study used an observational analytic with historic cohort design used kind of induction labor and women with post term as independent variable and success of vaginal delivery as dependent variable. The population are all of women with post term who had induction, sample size are 45 subject who had misoprostol by oral and 45 subject who had foley catheter. Data analysis used chi-square, percentage and risk relative. Result of this study showed that there are difference proportion of vaginal delivery used misoprostol by oral and foley catheter with risk relative 2,995, p-value 0,03 and Cl 95% (1 ,090 - 8,233) which means women who had misoprostol by oral as induction have 2,995 time more success than used foley catheter.